REVISITING JUSTIFICATION OF TECHNO-ECONOMIC LEVEL OF AGRICULTURAL MACHINES AND EQUIPMENT - A. Yu. Izmailov; V. A. Makarov (Сельскохозяйственные машины и технологии)
In recent years, a large amount of technology and equipment of both domestic and foreign production for agriculture comes in Russia. However, neglected domestic printing techniques justification technical-and-economic level (TEL) used machinery and equipment is not given. The authors outline ways to improve efficiency of agricultural production with use of techno-economic indicators system aimed at machinery improving. TEL means the relative quantitative characteristic of the machines and the degree of improvement of its performance and economic indicators compared to the characteristics of the basic option. When carrying out researches the program and target principle, and also Bayesian approach in the conditions of use of small samples were applied. Absent the parametrical characteristic for the developed machines and equipment, as an indicator of technical and economic level serves the coefficient of completeness of information. It is determined taking account the list of indicators, their importance (ponderability), interpretation and the analysis of TEL that is necessary for development of recommendations for decision making. Use of a technique hypothesizes that the importance of single indicators relative to one characteristic is the same and is equal to one. As indicators have probabilistic character, the researcher should consider the values received in various conditions. TEL is the overall index of enhancement of the estimated machine or equipment and is calculated on the corresponding formulas and criteria. The technique allows to determine objectively TEL of the current and future machines and equipment, and the analysis of components gives the chance to reveal allowances of increase in efficiency of various technological means.